Optimalisasi Penjualan dan Pendampingan Digital Marketing Guna Peningkatan Daya Beli Konsumen Bagi Sektor UMKM Penjahit Anis Berkah - Wefa, Muhammad Ali; Pabulo, Azfa Mutiara Ahmad (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2025)
MSMEs play a crucial role in Indonesia’s economy, yet challenges in digital adaptation often hinder their growth and competitiveness. This digital marketing assistance program aims to enhance the sales of Anis Berkah Tailor through effective branding and the use of digital platforms. The program began with in-depth interviews to identify the needs and challenges of the MSME, followed by assistance in designing a logo to serve as a visual identity representing its business values. The next phase involved creating and managing Instagram and Facebook accounts, emphasizing optimized profile settings and engaging content strategies. The results revealed that the new logo improved the business's professionalism and visual appeal, while social media expanded market reach and enhanced consumer engagement. Additionally, training on digital platform features provided valuable insights for the MSME owner, enabling more effective utilization of online marketing opportunities. With the right strategies in place, Anis Berkah Tailor is expected to achieve sustained productivity, competitiveness, and revenue growth.